Exploring the Benefits of Learning Applications in Increasing Achievement and Motivation in Islamic Religious Education - Agus Susanti; Li Jie; Siti Mahmudah; Erni Yusnita; Chandra Halim (Journal Neosantara Hybrid Learning, 2024)
Learning Islamic education is one of the learning points that can shape the character, morality, and spirituality of individuals in society. However, as time progresses, many challenges appear such as the lack of interest and involvement of students in learning Islam, especially in the current digital era. Limited time, lack of adequate resources, and changing students' mindsets towards media and technology are the main obstacles in achieving the goals of Islamic education. In addition, with the increasing development of information and communication technology, there is a demand to integrate technology into the learning process in order to update teaching methods and motivate students in learning Islam. The purpose of this research is to explore the potential of learning applications as an effective tool in improving the performance and motivation of students in Islamic religious education, taking into account contemporary challenges and needs in the religious learning process. The research method used is a quantitative method. The research data was obtained from the results of the questionnaire. The results of the research show that the use of learning applications significantly increases students' understanding of Islamic religious material, with the average test score increasing significantly. In addition, the level of student motivation in learning Islam also experienced a significant increase, evident from active participation in class discussions, task completion, and better attendance levels. The implementation of this research states that learning applications provide clear benefits in improving student performance and motivation in Islamic religious education. This confirms the need for technology integration in the learning process of Islamic Religion to optimize the student's learning experience and strengthen religious values ??in an increasingly digitally connected society.